KOMUNIKATOR DALAM STRATEGI ENDORSEMENT (Studi Strategi Endorsement Produsen Kerudung Voal di Instagram) - Puspanidra, Tiara; Valdiani, Dini (Media Bahasa, Sastra, dan Budaya Wahana, 2018)
Abstract The increasing use of Instagram as a social media that is used as a marketing tool raises a new promotion strategy, namely endorsement. Veil producers use endorsers as communicators in this strategy. The selection of endorsers in this study was seen from two criteria, attractiveness and credibility. This study uses a descriptive research method with a qualitative approach. The study was conducted in May-August 2018 in Bandung. The subjects in this study were voal veil producers, Tina Krisnandy, the main owner of Rahina Indonesia and Delita Nursyahfitri Amalia, the owner of Syamaita. Subject research through purposive sampling. The conclusion of this study is that there are differences in the use of endorsement in both voal veil producers where for large producer endorsement is not the main strategy of promotion while for medium producer is the opposite. For producers the attractiveness factor of communicators is a great influence on consumers. As for consumers, despite recognizing the influence of the endorser's attractiveness, they also attach importance to credibility. Keywords : endorsement, endorser, communicator, attractiveness, credibility